Foreign body in the male urethra: case report - Vagholkar, Ketan; Prajapat, Sourabh; Hamdule, Aamina; Narang, Narender; Bhatnagar, Isha (International Surgery Journal, 2023)
Cases of self-inserted foreign bodies into the lower urinary tract are uncommon. They are associated with a mental illness called polyembolokoilomania. The site, size and nature of the foreign body determines both the symptomatology and complications. A case of self-inserted needle into the penile urethra by a 15-year-old boy is presented. A plain X-ray of the pelvis revealed the needle. The needle was successfully removed by cystoscopy. Plane X-ray imaging and CT scan are essential to locate the site, size, and nature of the foreign body. Endoscopic approach is preferred in majority cases. Psychiatric counselling in the post-operative period is required to prevent further episodes of reinsertion of such foreign bodies.